A dried blood spot update: still an important bioanalytical technique?. (April 2013) - Spooner, Neil
This article discusses the benefits of dried blood spot sampling and the recent issues that have emerged when this technique is used in the regulated quantitative bioanalytical environment. The author explores what the way forward might be for this important technique and what some of the unexpected benefits of this change in sampling methodologies have been.